2013
DOI: 10.1159/000353151
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Development of Chronic Pouchitis after Ileal Pouch-Anal Anastomosis in Ulcerative Colitis

Abstract: Background: No previous studies have examined predictive factors for chronic pouchitis after ileal pouch-anal anastomosis (IPAA) for ulcerative colitis (UC) with consideration of changes in pouchitis subtypes during follow-up. This study evaluated the independent predictive factors for chronic pouchitis. Methods: A total of 244 consecutive patients who underwent IPAA were enrolled. We assessed the possible associations between pouchitis and clinical factors using Cox proportional hazard regression. Results: 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…No relevant RCTs were retrieved. Nine and 11 observational studies were selected for the analysis of chronic pouchitis and overall pouchitis respectively in relation to EIMs ( Table S1 , supporting information), and six and ten studies respectively in relation to PSC ( Table S2 , supporting information). One study included both ulcerative colitis and familial polyposis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No relevant RCTs were retrieved. Nine and 11 observational studies were selected for the analysis of chronic pouchitis and overall pouchitis respectively in relation to EIMs ( Table S1 , supporting information), and six and ten studies respectively in relation to PSC ( Table S2 , supporting information). One study included both ulcerative colitis and familial polyposis.…”
Section: Resultsmentioning
confidence: 99%
“…Although PSC is one of the most frequently occurring EIMs in Western countries, the incidence of PSC is reported to be lower in Japan. In three articles from Japan, the incidence of PSC was too low to be incorporated in the pooled analysis assessing the effect of PSC on the development of pouchitis. Two Western studies investigated the effect of PSC and EIMs on the development of pouchitis.…”
Section: Discussionmentioning
confidence: 99%
“…73,74 A retrospective report in the largest series in Japan consisted of 772 patients with UC observed a 10% cumulative incidence of pouchitis at 10 years after surgery, 75 but it seemed to be a little lower than recent reports. Okita et al 76 reported that chronic pouchitis occurred in 28% of patients who underwent IPAA. Our recent data also indicate that the cumulative incidence at 10 years after IPAA is approximately 30% and 20% for overall and chronic pouchitis, respectively.…”
Section: Incidence Of Pouchitis Among Different Countriesmentioning
confidence: 99%
“…Pouchitis has been shown to be associated with a longer duration of colitis [62,63] and is more common in patients with pancolitis [62], those requiring steroids before colectomy [64] and those with extra-intestinal manifestations [63], more specifically primary sclerosing cholangitis (PSC) [65]. A meta-analysis has shown anti-neutrophil cytoplasmic antibody to be associated with an increased risk of developing chronic pouchitis but not acute pouchitis [66].…”
Section: The Problematic Pouchmentioning
confidence: 99%